Thermomicrofluidics for biosensing applications. Issue 6 (16th May 2021) - Tian, Fei; Han, Ziwei; Deng, Jinqi; Liu, Chao; Sun, Jiashu
Abstract: The accurate detection of biological systems containing biomolecules and bioparticles is increasingly important in diverse research fields, particularly in analytical and biological chemistry. Implementing thermophoresis in microfluidic devices (thermomicrofluidics) enables the manipulation and measurement of biomolecules and bioparticles in a label‐free and high‐precision manner, providing a promising avenue for biosensing. This review presents fundamentals of thermophoresis and its coupling with other thermal‐induced physical phenomena in the microfluidic setups. We overview the capabilities of thermomicrofluidics for diverse biosensing applications such as monitoring of biomolecular interactions, detection of nucleic acids, profiling of extracellular vesicles, and manipulation of cells. Biosensing by thermomicrofluidics provides insights into physiopathological processes and disease diagnostics. Current challenges and further directions of thermomicrofluidic detection are discussed. Abstract : Implementing thermophoresis in microfluidic devices (thermomicrofluidics) enables the precise manipulation and measurement of biomolecules and bioparticles. In this review, the authors overview the capabilities of thermomicrofluidics for diverse biosensing applications.